The protective effects of adenosine deaminase inhibitor and ouercetin against hepatocellular carcinoma induced by thioacetamide in male rats via downregulation of iNOS, Ki67 and Pan-CK - Magdy, Marwa; M. Omar, Hossam El-Din; Abdel- Ghaffar, Sary Kh.; Ibrahim, Ahmed Th. (Open Science Journal, 2021)
The liver is the largest and most vulnerable organ in the body, several factors can cause liver cirrhosis and the onset of hepatocellular carcinoma. This study aims to investigate the possibility for adenosine deaminase inhibitor (EHNA) which reduces liver injury, neutrophil infiltration and the levels of proinflammatory cytokines and also it is considering as a target of liver cirrhosis and beginning of hepatocellular carcinoma protective, quercetin which is one of the most common flavonoids has an antioxidant, antitumor and chemopreventive effect on the liver-induced preneoplastic lesions and their combination against thioacetamide as a hepatotoxic and a carcinogenic compound. Biochemical, histopathological and immunohistochemical studies were carried out on male albino rats model to evaluate this possibility. Thioacetamide-treated rats showed a significant increase in liver function tests, alpha-fetoprotein level, expression of inducible Nitric Oxide Synthesis (iNOS), Ki67 and Pan-Cytokeratin (Pan-CK) in hepatic tissue of rats. The results of the present study show that treatment with quercetin, EHNA or their combination attenuated changes in liver functions, histopathological changes, reduced collagen deposition and decreased the expression of iNOS, Ki67 and Pan-CK induced by thioacetamide.